2020
DOI: 10.1038/s41598-020-62109-5
|View full text |Cite
|
Sign up to set email alerts
|

Fully Automated Molecular Diagnostic System “Simprova” for Simultaneous Testing of Multiple Items

Abstract: Nucleic acid amplification-based diagnostics is known as one of the molecular diagnostic systems that allows higher sensitive detection of pathogens than test methods such as immunoassay. However, it has not been widely used because it is complicated to use and takes a long time to generate results. on the other hand, development of fully automated molecular diagnostic systems has been growing around the world as demand for such systems from physicians and laboratory technicians has increased. to meet this dem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…In conclusion, the newly developed LAMP-based POCT "Simprova" for IV, RSV, and hMPV demonstrated high sensitivity and high specificity in clinical specimens from patients with influenza-like illnesses. This Simprova-RV processed the entire step automatically; the test can be performed without skilled personnel in the POC setting by simply placing a pretreatment cartridge, a testing chip, and the sample in the machine 19 . In addition, positive results can be achieved faster than by rPCR testing, because of the use of an isothermal nucleic acid amplification method.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In conclusion, the newly developed LAMP-based POCT "Simprova" for IV, RSV, and hMPV demonstrated high sensitivity and high specificity in clinical specimens from patients with influenza-like illnesses. This Simprova-RV processed the entire step automatically; the test can be performed without skilled personnel in the POC setting by simply placing a pretreatment cartridge, a testing chip, and the sample in the machine 19 . In addition, positive results can be achieved faster than by rPCR testing, because of the use of an isothermal nucleic acid amplification method.…”
Section: Discussionmentioning
confidence: 99%
“…Simprova-RV was performed using a principal machine in which the pretreatment (extraction and purification of nucleic acid from the sample) part and the LAMP reaction and detection part were separated in this study. Simprova-RV was carried out as described previously 19 . In the pretreatment Purification Kit (Thermo Fisher Scientific) using 200 µL of UTM mixed with clinical specimens according to the manufacturer's instructions, with an elution of 50 µL.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study demonstrated the possibility to fully automate LAMP methods for the rapid and effortless molecular diagnosis [98], which may pave a way to the automation of RT-LAMP based COVID-19 diagnosis. In this system called "Simprova" (Developed by Eiken Chemical Co., Ltd.), a central unit that controls the entire system, a pretreatment unit that isolates and purifies nucleic acid from samples, and the LAMP component to detect and amplify nucleic acid sequences were all integrated.…”
Section: Challenges and Prospectsmentioning
confidence: 99%
“…The Eiken Chemical Co. in Japan has developed a system for multiple testing that combines sample preparation with LAMP, and the optical detection of the results with RNA purification is based on magnetic force ( Fig. 4 A) [ 89 ]. It employed a microfluidic cartridge with 25 wells, allowing for multiplexed detection.…”
Section: Quo Vadis Portable Viral Detection?mentioning
confidence: 99%